Mutations in TGFBR2 gene cause spontaneous cervical artery dissection. Issue 12 (26th January 2011) - Pezzini, Alessandro; Drera, Bruno; Del Zotto, Elisabetta; Ritelli, Marco; Carletti, Monica; Tomelleri, Gianpaolo; Bovi, Paolo; Giossi, Alessia; Volonghi, Irene; Costa, Paolo; Magoni, Mauro; Padovani, Alessandro; et al.
Abstract : Mutations in the genes encoding transforming growth factor β receptors 1 and 2 ( TGFBR1 and TGFBR2 ) have recently been associated with hereditary connective tissue disorders with widespread vascular involvement, including arterial dissection. To determine whether mutations in these genes cause spontaneous cervical artery dissection (sCAD), all coding exons of TGFBR1 and TGFBR2 were sequenced in 56 consecutive patients with sCAD. Novel TGFBR2 disease causing mutations were found in two patients. The two mutations were the pK327R substitution affecting the kinase domain of TGFBR2 and the pC138R substitution falling in the extracellular domain of the protein, involved in TGFβ binding and signalling. No TGFBR1 mutation was found. The findings indicate that TGFBR2 gene mutations are responsible for sCAD in 3.6% (95% CI 0.0 to 8.4) of cases, have implications in understanding the role of TGFβ signalling in the pathogenesis of sCAD and emphasise the importance of considering molecular characterisation of the TGFBR2 gene in these patients, regardless of the presence of clinical features suggestive of hereditary connective tissue disorders.